End effects of a thermoacoustic stack plate on the flow pattern - Mohd. Ghazali, Normah (2015)
Thermoacoustic cooling technology has gained attention in the last few decades due its environmentally friendly system. The absence of any refrigerant and a compressor to generate cooling is indeed desirable but the performance to date has yet to attain a competitive magnitude. Significant cooling effects are still difficult to achieve possibly due to the design and fabrication of the stack, the heart of the thermoacoustic cooling system. The geometry, stack spacing and stack separation are important parameters that have been shown to greatly affect the thermoacoustic effects. In particular, experience with design, fabrication, and testing with parallel plate stack have proven that the final parallel stack product could make or fail the cooling effects. This paper reports a simulation study on the end effects of the parallel stack plate on the fluid flow and temperature patterns surrounding the stack. A two-plate parallel stack with negligible thickness is modeled and the system of Navier-Stokes equations is solved with finite difference method using a specifically developed MATLAB code. Plates with straight and slightly curved edges have been simulated, the latter have not been reported before. Results show that streamlines are much disturbed and vortices developed faster even with the slight tilt of the edges. These indicate that imperfectly fabricated parallel stack plates could be the cause of the failure to achieve the desired designed cooling effects.